Implementation of land acquisition laws and procedures in Zanzibar : issues and solutions - Hikmany, Abdul-Nasser Hamed Rashid (Ahmad Ibrahim Kulliyyah of Laws, International Islamic University Malaysia, 2017)
The Constitution of Zanzibar 1984 permits the government of Zanzibar to acquire private land rights for defence, security, health, planning and development. It is observed that article 17 of the Constitution of Zanzibar 1984 prescribes three main conditions relating to land acquisition. These are the conditions of importance, public interest and payment of a fair and adequate compensation. The right of acquiring lands by the government is subsequently regulated under basic land acquisition laws namely the Land Acquisition Decree 1909, Acquisition of Land (Assessment of Compensation) Decree 1949 and Land Tenure Act 1992. Since the Constitutional conditions are not provided for in detail under the land acquisition laws, they remain to be controversial issues that need to be critically analysed for the purpose of recommending solutions. This research aims to examine and analyse land acquisition laws and procedures in Zanzibar through a qualitative legal research method; such as legislation, case laws, journal articles and textbooks. Fifty five (55) interviews were also conducted consisting of 3 Zanzibar High Court advocates, 4 Sheha (area administrators), 6 Judges and Magistrates, 16 officers at the Zanzibar Ministry of Lands, 13 deprived land holders, 2 District Commissioners, 2 State Attorneys, 3 private professionals, 3 Non-Governmental Organisations and 3 other government officers. Case studies were conducted on selected land acquisition cases to find out the reality and practice of land acquisition in Zanzibar. This research additionally examines the general principles of Islam relating to land acquisition laws, procedures, implementation and case studies for the purpose of adopting the best practices. It is discovered that several issues arise in the implementation of land acquisition laws and procedures in Zanzibar including conflict within the land acquisition laws, lack of adhering to the Constitutional requirements of a fair and adequate compensation, inconsistency in valuing private lands for compensation, failure to issue or publish notices, and unethical conducts by land acquisition officers. It is resolved that there is a need to amend article 17 of the Constitution of Zanzibar, enact a new law for land acquisition and revise land acquisition related laws as well as judiciary proceedings. The new land acquisition law should redefine the land acquisition concepts, introduce a centralised land acquisition authority, make the purpose of acquisition more reasonable, disclose the elements of a fair and adequate compensation, reassess the principles of valuation and safeguard the interests of all stakeholders. Other recommended solutions include borrowing experiences from Islam and raising awareness of land acquisition officers on laws and procedures.